Analisis Kesalahan Murid dalam Memahami Konsep SPLTV pada Masalah Kontekstual Berdasarkan Teori Clements dan Ellerton - Jihan Rofifah; Wardani Rahayu; Mimi Nur Hajizah (Pendidikan Matematika FKIP Universitas Mataram, 2026)
Conceptual understanding is a crucial foundation in algebra learning, particularly in the topic of Systems of Linear Equations in Three Variables (SLETV), which requires mathematical representation, logical reasoning, and appropriate procedural selection. This study aims to analyze students’ errors in conceptual understanding when solving contextual SLETV problems based on the error analysis theory proposed by Clements and Ellerton. A qualitative descriptive approach was employed involving 36 tenth-grade students from a senior high school in North Jakarta. Data were collected through a conceptual understanding test as a preliminary study and a contextual SLETV problem-solving test as the main instrument. Two students were selected as key subjects, representing high and low levels of conceptual understanding. The findings indicate that students with high conceptual understanding made relatively minimal and partial conceptual errors. In contrast, students with low conceptual understanding predominantly exhibited conceptual, procedural, and application errors. Furthermore, the ability to represent concepts mathematically and to select and apply appropriate solution procedures emerged as the weakest indicators. These results confirm that insufficient conceptual understanding significantly contributes to students’ errors in solving contextual SLETV problems.